2023
DOI: 10.1101/2023.02.24.529902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human immune phenotyping reveals accelerated aging in type 1 diabetes

Abstract: The composition of immune cells in peripheral blood is dramatically remodeled throughout the human lifespan, as environmental exposures shape the proportion and phenotype of cellular subsets. These dynamic shifts complicate efforts to identify disease-associated immune signatures in type 1 diabetes (T1D), which is variable in age of onset and rate of beta-cell decline. Herein, we conducted standardized flow cytometric immune profiling on peripheral blood from a cross-sectional cohort of T1D participants (n=240… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 109 publications
(161 reference statements)
0
6
0
Order By: Relevance
“…Therefore, profiling the immune system in individuals with high genetic risk may uncover immune perturbations associated with T1D disease susceptibility. Using the HLA portion of Genetic Risk Score 2 (GRS2) 68 , we generated an HLA genetic risk score (HLA-GRS) that accounts for HLA DR-DQ haplotype interactions 17,68 , with a higher score indicating a higher risk for disease development. As expected, T1D donors had increased HLA-GRS compared to ND (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, profiling the immune system in individuals with high genetic risk may uncover immune perturbations associated with T1D disease susceptibility. Using the HLA portion of Genetic Risk Score 2 (GRS2) 68 , we generated an HLA genetic risk score (HLA-GRS) that accounts for HLA DR-DQ haplotype interactions 17,68 , with a higher score indicating a higher risk for disease development. As expected, T1D donors had increased HLA-GRS compared to ND (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…As T1D progresses, β cell destruction is thought to accelerate along with proinflammatory signaling, peaking at T1D onset. Long-term inflammation drives immune aging, activation, and differentiation signatures in PBMCs of T1D donors 17 . We found that these immune activation-associated changes also occur in pLN and mLN of T1D donors.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR3 has been described to be responsible for T-cell migration to inflamed tissue along a CXCR3 ligand-concentration gradient [ 34–36 ]. Specifically, CXCR3 was shown to be increased on various T-cell subsets in patients with type 1 diabetes, including naïve and EM CD8 + T-cells and follicular T helper cells [ 28 ]. Given that aCD3 treatment increased the relative proportion of circulating CD8 + T cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This effect could explain the transient effect of aCD3 monotherapy and, depending on the degree of escape, also the lack of response in a subgroup of patients. Even if CXCR3 was shown to be increased on various T-cell subsets in patients with type 1 diabetes, thus potentially having a detrimental effect on disease progression [ 28 ], some studies have reported reduced CXCR3 expression on blood T cells in individuals with long-lasting type 1 diabetes [ 39 ]. The conflicting results may rely on various factors such as differences in disease stages and methodologies used for CXCR3 expression assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation